Identifying Preference for Early Resolution from Asset Prices - Ai, Hengjie; Bansal, Ravi; Guo, Hongye; Yaron, Amir (American Economic Review, 2026)
This paper develops an asset market-based test for preference for the timing of resolution of uncertainty. Our main theorem provides a characterization of preference for early resolution of uncertainty in terms of the risk premium realized during the period when the informativeness of macroeconomic announcements is resolved. Empirically, we find support for preference for early resolution of uncertainty based on evidence on the dynamics of the implied volatility of S&P 500 index options before Federal Open Market Committee announcements. (JEL D81, D83, G13, G14, G41)